PENGARUH KONSUMSI HERBAL TERHADAP KONTRAKSI ALAMIAH PADA IBU BERSALIN - Muflihah, Ima Syamrotul (Universitas Harapan Bangsa Purwokerto, 2020)
ABSTRAC His or uterine contractions during labor is one of the factors that determine the progress of labor. Progress in labor is marked by an increase in the duration, intensity and frequency of uterine contractions accompanied by the progress of cervical thinning and the decline of the baby. One of the efforts made to improve his mother in labor is to induce labor. One of the community responses to this is the development of a habit of consuming plants that are believed to help launch labor. WHO has also allowed the use of medicinal plants as a form of alternative therapy, the use of which is tailored to the purpose and efficacy of plants. The purpose of quantitative research is to determine the benefits of the influence of herbs on natural contractions (his) in maternity and the purpose of qualitative research is the type of herbs consumed. The research methods are mixed methods sequential explanatory design. Pineapple is a natural material that most respondents consume to stimulate natural contractions that cause adequate contractions. Keywords: Herbs, Natural Contractions, delivery labor